Recovery of the groundwater of spent uranium deposits ore horizon during the remediation process - Blynskiy, P.A.; Panova, E.N.; Zhaksybekova, K.A.; Kenzhina, I.E. (Recent Contributions to Physics, 2017)
The pollution in underground leaching usually reduces to the impact on the earth's surface and aquifer harmful to human health and living nature of chemically active substances used and formed during the extraction of uranium from the subsoil. Although this pollution has local nature, it must be controlled both during the underground leaching process and after its completion during remediation. The main condition during remediation process on spent uranium deposits of the Republic of Kazakhstan, is return of used territories to their initial state. The main problem in this case is the high acidity of the underground horizon. The neutralization with alkaline solutions could be one of the solutions. It is proposed to use sodium hydroxide to accelerate the remediation of spent uranium deposits. The possibility of using purified sodium hydroxide of the first circuit of the BN-350 fast reactor facility was considered in this work. This paper presents the results of a study of the recovery of the ore horizon of spent uranium deposits in the Republic of Kazakhstan and its sorption properties with respect to technogenic radionuclides.